Universal Health Coverage in India: Challenges and Future Directions of Ayushman Bharat" (International Journal of Food and Nutritional Sciences, 2022)
The Ayushman Bharat initiative was started in the year 2018, aims to offer or provide India enormous population full health care. This study examines the scheme's design, implementation, and impact on rural healthcare in India. According to our research, the program or initiative has improved rural communities’ access to healthcare and financial security, but there are remain some issues, such as supply and market discrepancies, insufficient government funding for healthcare and inadequate rural health facilities. This editorial offers a comprehensive analysis of India's Ayushman Bharat program or initiative, a pioneering universal healthcare program designed or develop the design that tackles the country's healthcare disparities. The review examines the initiative's development, scope, implementation, and response to the COVID-19 pandemic. It showcases the program's achievements in expanding healthcare access, providing financial security, and upgrading healthcare infrastructure. The editorial also identifies key challenges, including mismatches between healthcare supply and demand, insufficient government funding, and difficulties in accessing quality healthcare in rural areas. By highlighting the initiative's benefits and challenges, this review aims to promote awareness and adoption among eligible beneficiaries, positioning Ayushman Bharat as a potential model for global healthcare equity.